Plant Poetics : Literary Forms and Functions of the Vegetal - Jacobs, Joela; Kranz, Isabel; Nitzke, Solvejg (Critical Plant Studies, 2025)
Plant Poetics explores the forms and functions of the vegetal across a broad body of literature. From Homer to Johann Wolfgang von Goethe and from Jamaica Kincaid to Esther Kinsky, the contributions to this volume trace plants in literary works from around the world. Based on nuanced theoretical and historical groundwork, these readings bring together interdisciplinary perspectives on literary and cultural plant studies. The volume shows how vegetal beings have impacted the ways humans think about narrative time, genre, and writing as a literary practice. Plant Poetics illustrates the capacity of plants to make (literary) worlds and shape their forms.